(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to: Identify the effectiveness of an educational design according to the thinking outside the frame model in decorative formations. Build an educational design according to the thinking outside the frame model.To achieve the research objectives, the researcher formulated the following hypotheses: There are no statistically significant differences at a significance level of (0.05) between the average ranks of the scores of the research sample students in the pre- and post-achievement test. There are no statistically significant differences at a level of (0.05) between the average ranks of the scores of the research sample students in the pre- and post-skill performance test.The research problem was represented in the following question: (What is the effectiveness of an educational design according to the (thinking outside the frame) model in decorative formations?) In addition to the importance of the research, which focused on (using this educational design may help students adapt to various decorative artistic challenges and think about them in an innovative, unconventional way).The research community consisted of fourth-grade students - Department of Calligraphy and Ornamentation in the Fine Arts Institutes in Iraq (Baghdad, Mosul, Diyala, Kirkuk) with a total of (92) students, while the research sample consisted of students of the Department of Calligraphy and Ornamentation - Institute of Fine Arts for Girls / Karkh 1 with a total of (15) students.The study was applied to the research sample after the researcher prepared the achievement test and the evaluation form for the decorative work and educational design according to the model of thinking outside the framework, and to show the results of the research, the researcher used the statistical package (spss) in analyzing the results of her research, which were as follows: Regarding the achievement test, the calculated MacGeorgian value of (0.65) is greater than the spoken MacGeorgian value of (0.60), which means that there are statistically significant differences between the averages of the pre- and post-achievement test, which confirms the effectiveness of the educational design in developing the achievement of the students of the research sample. Regarding the skill performance test, the calculated MacGeorgian value of (0.61) is greater than the reported MacGeorgian value of (0.60), which means that there are statistically significant differences between the averages of the pre- and post-skill performance test, which confirms the effectiveness of the educational design in developing the skill performance of the students in the research sample. The researcher reached a number of conclusions, the most prominent of which was: The educational design according to the model of thinking outside the framework led to an increase in the students’ interaction with the educational activities, which enhanced their interest in the subject of the art of decoration and their enjoyment of it, which was positively reflected in the level of their skill and academic performance. In continuation of the current research, the researcher recommended adopting the educational design according to the model of thinking outside the framework in teaching the subject of decorative art at the Institute of Fine Arts in order to enhance innovation and renewal in artistic work. The researcher suggested conducting studies, including: the effect of educational design according to the model of thinking outside the framework on achievement and the development of mental flexibility among students of the Department of Art Education in the subject of perspective